International relations of the Middle East - Fawcett, Louise L'Estrange (Oxford University Press, 2013)
This textbook offers an historical framework and up-to-date analysis of contemporary events in the Middle East. Bringing together leading scholars in the field, it presents a balanced and comprehensive assessment of the international politics of the region